Is Pseudobutyrivibrio xylanivorans strain Mz5T suitable as a probiotic? An in vitro study - Cepeljnik, T; Zorec, M; Kostanjsek, R; Nekrep, F V; Marinsek-Logar, R (Folia microbiologica, 2003)
Rumen bacterium Pseudobutyrivibrio xylanivorans strain Mz5T possessed a potent xylanolytic enzyme system consisting of at least 7 different xylan hydrolases with molar mass 27-145 kDa. Three of them were successfully isolated in active native form. This strain produced butyrate and lactate on different saccharides. cis-9, trans-11-Conjugated linoleic acid was also detected in the culture medium. Bacteriocin-like inhibitory substances of Mz5T were active against some strains of rumen bacteria and against selected Salmonella and E. coli isolates from poultry meat. The strain Mz5T retained viability and xylanolytic activity also under not fully anaerobic conditions; its cells attached to the Caco-2 cells so that its successful association with gut epithelial cells may be expected. These in vitro results confirmed several probiotic traits of the isolate Mz5T and justified further in vivo experiments to test its ability to improve animal health and performance.
Keywords: Caco-2 Cells; Butyrates; In Vitro Techniques; Bacterial Adhesion; kyselina mléčná; gramnegativní anaerobní tyčinky rovné, zakřivené a spirálovité; Caco-2 buňky; drůbež; Salmonella; maso; Lactic Acid; bakteriociny; probiotika; techniky in vitro; bakteriální adheze; skot; Probiotics; Bacteriocins; Xylosidases; Escherichia coli; ženské pohlaví; xylosidasy; zvířata; butyráty; Humans; Linoleic Acid; Poultry; bachor; Meat; Cattle; Gram-Negative Anaerobic Straight, Curved, and Helical Rods; Rumen; Female; kyselina linolová; lidé; Animals